2014
DOI: 10.1080/01650521.2014.962950
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of leafhoppers (Hemiptera: Cicadellidae) in experimental rice lots and associated weeds in Buenos Aires province, Argentina

Abstract: We identified the species of Cicadellidae associated with rice fields from an agricultural experimental station of La Plata city, Argentina, and explored the diversity pattern of the leafhopper assemblage. Insects were obtained from rice and surrounding weeds between 2006 and 2010. Syncharina argentina (Berg) and Agalliana ensigera Oman were the most abundant species in rice and weeds, respectively. Diversity (H′), heterogeneity (D) and evenness (J) indices were estimated. There was a significant effect of cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
1
0
2
Order By: Relevance
“…Contrastingly, Mutlu et al (2016) observed that weeds increased the population of cicadellids in rice fields as 71.4% of individuals were recorded from weedy fields, whereas 28.6% were noted from weed-free fields. On the other hand, Paradell et al (2014) reported that weeds resulted in significantly higher leafhopper species from rice fields. Similar studies in different crops have reported that certain weeds (such as Johnson grass, purslane, nutgrass and common cocklebur) significantly increase the population of Cicadellidae, indicating the necessity of weed control (Andow, 1992;Margues et al, 2012;Mutlu and Sertkaya, 2015a).…”
Section: Resultsmentioning
confidence: 99%
“…Contrastingly, Mutlu et al (2016) observed that weeds increased the population of cicadellids in rice fields as 71.4% of individuals were recorded from weedy fields, whereas 28.6% were noted from weed-free fields. On the other hand, Paradell et al (2014) reported that weeds resulted in significantly higher leafhopper species from rice fields. Similar studies in different crops have reported that certain weeds (such as Johnson grass, purslane, nutgrass and common cocklebur) significantly increase the population of Cicadellidae, indicating the necessity of weed control (Andow, 1992;Margues et al, 2012;Mutlu and Sertkaya, 2015a).…”
Section: Resultsmentioning
confidence: 99%
“…Diğer iki familyadaki birey sayıları yabancıotlu-otsuz karakterde sayısal olarak yakın değerler elde edilmiş ve yabancıotların bu iki familyanın popülasyon yoğunluğu üzerinde önemli bir etkisinin olmadığı sonucuna varılmıştır. Cicadellidae familyası için elde edilen sonucu destekler nitelikte, Paradell et al (2014), çeltikte yabancıotlar üzerinde %83, yabancıotsuz alanda ise %17 oranında yaprakpiresi belirlediklerini ve yabancıotlu alanların çeltikten daha fazla yaprakpiresi toplandığını bildirmişlerdir. Yabancıotlu ve otsuz alanlardan elde edilen verilere yapılan varyans analizi Çizelge 2 ve 3'te verilmiştir.…”
Section: Yaprakpiresi Türlerinin Belirlenmesiunclassified
“…Zea mays 'corn', Triticum aestivum 'wheat', Avena sativa 'oat' and associated weeds (Paradell 1995), Sorghum vulgare (Pers.) The genus Plesiommata in Argentina 67 'sorghum' (de Remes Lenicov et al 2006), rice (Paradell et al 2014), Brassica sp., Lycopersicon sp., Solanum sp. (Maes & Godoy 1993), Citrus sinensis 'sweet orange' and associated weeds (Remes Lenicov et al 1999), C. reticulata 'tangerine hybrid' (Dellapé 2013), Andropogon gayanus (Toledo et al 1989), weeds associated with Carica papaya (Lozada Robles & Arellano Cruz 2008).…”
Section: Host Plantsmentioning
confidence: 99%